2020
DOI: 10.1038/s41419-020-02953-5
|View full text |Cite
|
Sign up to set email alerts
|

CHIP as a therapeutic target for neurological diseases

Abstract: Carboxy-terminus of Hsc70-interacting protein (CHIP) functions both as a molecular co-chaperone and ubiquitin E3 ligase playing a critical role in modulating the degradation of numerous chaperone-bound proteins. To date, it has been implicated in the regulation of numerous biological functions, including misfolded-protein refolding, autophagy, immunity, and necroptosis. Moreover, the ubiquitous expression of CHIP in the central nervous system suggests that it may be implicated in a wide range of functions in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 127 publications
(204 reference statements)
1
37
0
Order By: Relevance
“…(F) Immunoprecipitation assay was used to detect the interaction between EGLN2 N88 and MDM2 in MIAT-knockdown primary rat neurons with 12 h reoxygenation after OGD treatment of some chaperone-bound proteins. 26 NDFIP1 binds to PTEN and enhances its ubiquitination mediated by NEDD4 and nuclear import, thereby promoting neuronal survival following cerebral ischaemia. 27 Therefore, it is necessary to consider the specific functions of ubiquitin ligases in stress regulation and neuronal degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…(F) Immunoprecipitation assay was used to detect the interaction between EGLN2 N88 and MDM2 in MIAT-knockdown primary rat neurons with 12 h reoxygenation after OGD treatment of some chaperone-bound proteins. 26 NDFIP1 binds to PTEN and enhances its ubiquitination mediated by NEDD4 and nuclear import, thereby promoting neuronal survival following cerebral ischaemia. 27 Therefore, it is necessary to consider the specific functions of ubiquitin ligases in stress regulation and neuronal degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, JNPL3 mice with P301L tau overexpression exhibit decreased CHIP levels in their spinal cords, increased tau inclusions, and neuronal loss, whereas their cerebellar regions demonstrated increased CHIP expression ( Sahara et al, 2005 ). Zhang et al (2020) showed that CHIP can directly bind, attach K48- and K63-linked ubiquitin, and eliminate phosphorylated tau, inducing both proteasomal and autophagic degradation ( Joshi et al, 2016 ). CHIP also interacts with caspase-cleaved tau and is involved in its degradation in cortical neurons ( Dolan and Johnson, 2010 ).…”
Section: E3 Ligases With Expression Changes In Alzheimer’s Diseasementioning
confidence: 99%
“…There are numerous implications for the dysregulation of Hsp70 leading to diseases 165,166 These include cancer, 162 central nervous system (CNS) disorders, 167 and cardiovascular diseases. 168 Moreover, the co-chaperones BAG, 105,169,170 Hsp40, 171,172 Hip, 138 HOP, 173 HspBP1, 174 HSP110, 175,176 CHIP, [177][178][179] and SAMDs 162,164 are also implicated in wide variety of diseases. The implications of Hsp70 and co-chaperones in wide range of diseases have led to calls to target these proteins for drug discovery.…”
Section: Insights On Drug Discovery and Therapeutic Targetingmentioning
confidence: 99%